Chiari III malformation: imaging features. - Castillo, M; Quencer, R M; Dominguez, R (American Journal of Neuroradiology, 1992)
PURPOSE To analyze and discuss the MR and CT features of Chiari type III malformations.PATIENTS AND METHOD MR and CT studies in nine neonates born at term with Chiari type III malformations were retrospectively reviewed.RESULTS High cervical/low occipital encephaloceles were present in all cases. Hypoplasia of the low and midline aspects of the parietal bones was seen in four patients. The encephaloceles contained varying amounts of brain (cerebellum and occipital lobes, six cases; cerebellum only, three cases), ventricles (fourth, six cases; lateral, three cases), cisterns, and in one case, the medulla and pons. Associated anomalies included: petrous and clivus scalloping (five cases/nine cases), cerebellar hemisphere overgrowth (two cases/nine cases), cerebellar tonsillar herniation (three cases/seven cases), deformed midbrain (nine cases), hydrocephalus (two cases/nine cases), dysgenesis of the corpus callosum (six cases/nine cases), posterior cervical vertebral agenesis (three cases/eight cases), and spinal cord syrinxes (two cases/seven cases). In four patients who underwent surgical resection and closure, aberrant deep draining veins and ectopic venous sinuses within the encephaloceles were found. Pathology examination of the encephalocele (four cases/nine cases) showed multiple anomalies (necrosis, gliosis, heterotopias, meningeal fibrosis) that were not demonstrable by either MR or CT. The marked disorganization of the tissues contained within the cephalocele may account for the lack of MR sensitivity to these abnormalities.CONCLUSION Preoperative determination of the position of the medulla and pons is essential and is easily accomplished by MR. To avoid surgical complications, the high incidence of venous anomalies should be kept in mind.